A facile patterning of silver nanowires using a magnetic printing method. (5th August 2015) - Ahn, Taebin; Kim, Han-Jung; Lee, Jihye; Choi, Dae-Geun; Jung, Joo-Yun; Choi, Jun-Hyuk; Jeon, Sohee; Kim, Jong-Duk; Jeong, Jun-Ho
Abstract: Patterning of metal nanowires (NWs) is vital for the fabrication of NW-based, high-performance devices such as sensors, transparent conducting electrodes, and optoelectronics. However, the majority of existing patterning methods require complex and expensive technologies. For this reason, we report for the first time a facile and quick patterning method of silver (Ag) NWs using a magnetic printing method. We successfully demonstrated a patterned AgNW grid structure on a flexible substrate as transparent electrodes. The flexible AgNW grid electrode exhibited optical and electrical properties comparable to those of commercial transparent conducting electrodes. We believe our work will be broadly applicable to other NW-based devices such as sensors, energy storage devices, metadevices, nanoscale electronics, and optoelectronics.